ANALISIS KETERAMPILAN PROSES SAINS PADA BUKU SEKOLAH ELEKTRONIK IPA SMP KELAS VII, VIII DAN IX - Fauziyah Naviyati; Elok Sudibyo (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This study was conducted with the aim of knowing the level of representation of Science Process Skills (SPS) in the seventh, eighth and ninth grade science electronic schoolbooks published by the Center for Curriculum and Books. The research method used is descriptive quantitative with coding system. The objects in this study were the Class VII, VIII and IX IPA Electronic School Books (BSE) with the criteria for the 2013 curriculum books published by the Center for Curriculum and Books in the form of electronic books. The instrument used in this study was the observation sheet used to analyze the availability of aspects of Science Process Skills. The data analysis technique used iscontent analysis. The results from this study are indicators of science process skills (SPS) which are available in different books. In the three books, the most common indicator is data interpretation with an average percentage of 87.63%, then formulating hypotheses with an average percentage of 8.26%, designing experiments with an average percentage of 3.42%, and for indicators formulate a problem with an average percentage of 1.6%. Suggestions from researchers are books to be published should contain a better indicator of a science process skills integrated at a greater proportion than a basic science proses skills to identify a science process skill a a junior high school level before heading for the higher ranks.